The Effect of the Role of Youth on the Development of Pantai Alam Datuk Tourism Batu Bara District - Anugrah, Ridho; Revida, Erika; Purwoko, Agus (Journal of Environmental and Development Studies, 2021)
The tourism plays a very important role in promoting economic growth, contributing to creating jobs and reducing poverty. The tourism industry is also one of the fastest growing sectors, contributing 9.1% of GDP. UU no. 40 of 2009 Article 6 concerning Youth, plays an active role in all aspects of national development, mobilizes moral strength, social mastery and advances change. Therefore, it is important for youth in tourism development, especially the extent of the role of youth in tourism development, in this case at Pantai Alam Datuk, Batu Bara Regency. The purpose of this study was to analyze the effect of the role of youth as an agent of change, agent of development and agent of modernization partially and simultaneously influencing the tourism development of Pantai Alam Datuk, Batu Bara Regency. This research took place at Pantai Alam Datuk, Sei Suka District, Batu Bara Regency with 81 youths aged 18 to 30 years as a sample. The method used is a quantitative descriptive approach with purposive sampling technique. The data analysis used is multiple linear regression along with data collection techniques using a closed questionnaire which is measured by a Likert scale, interviews and documentation studies. The results of the research show that the role of youth as an agent of change and agent of development partially affects the development of Pantai Alam Datuk tourism, while the role of youth as an agent of modernization partially has no effect on the development of Pantai Alam Datuk tourism in Kwala Indah Village, Sei Suka District. Batu Bara Regency.